Copper and prion diseases. (August 2002) - Brown, D. R.
Abstract : Transmissible spongiform encephalopathies are diseases of animals and humans that are also termed prion diseases. These diseases are linked together because a normal brain glycoprotein termed the prion protein is converted to a readily detectable protease-resistant isoform. There is now strong evidence to suggest that apart from this difference in resistance a major difference between the isoforms is that the normal prion protein binds copper and has an anti-oxidant function. Brains from Creutzfeldt-Jakob disease patients and brains from mice with experimental mouse scrapie have been shown to have changes in the levels of both copper and manganese. There is growing evidence that links prion diseases to disturbances of metal metabolism.